2021
DOI: 10.1002/mame.202100461
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Covalent Triazine‐Based Frameworks via Friedel–Crafts Reactions of Cyanuric Chloride with Thienyl and Carbazolyl Derivatives for Fluorescence Sensing to Picric Acid, Iodine and Capturing Iodine

Abstract: A multifunctional thiophene-based covalent triazine framework (TTPATTh) with triphenylamine as core is synthesized by Friedel-Crafts reaction of cyanuric chloride with thienyl derivative for the first time. The yield of TTPATTh (99.59%) is far higher than that of the carbazole-based CTF (TTPATCz, 47.03%). TTPATTh and TTPATCz possess high BET surface areas with 1235 and 2501 m 2 g -1 as well as high pore volumes with 1.60 and 2.23 cm 3 g -1 , respectively. TTPATTh and TTPATCz have high thermal stability with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The BET surface area and pore volume were found Scheme 10 Schematics for the synthesis of TTPATTh and TTPATCz. 54 to be 481.1 m 2 g À1 and 0.710 cc g À1 , respectively. Morphological studies show a regular spherical morphology, which was obtained as a result of cross edge-to-edge interaction of precursors.…”
Section: Schiff's Base Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The BET surface area and pore volume were found Scheme 10 Schematics for the synthesis of TTPATTh and TTPATCz. 54 to be 481.1 m 2 g À1 and 0.710 cc g À1 , respectively. Morphological studies show a regular spherical morphology, which was obtained as a result of cross edge-to-edge interaction of precursors.…”
Section: Schiff's Base Methodsmentioning
confidence: 96%
“…Very recently in 2021, Tong et al reported two multifunctional COPs named as TTPATTh and TPATCz triazine-thiophene-based polymeric materials through the Friedel-Crafts polymerization of cyanuric chloride with TPATTh (tris[4-(2-thienyl)phenyl]amine) and TPATC (tris[4-carbazoyl-9-ylphenyl]amine). 54 This report presents an effective application of Friedel-Crafts arylation reaction using methanesulfonic acid (CH 3 SO 3 H) as the catalyst to synthesize a thiophene-fused covalent triazine polymeric network (Scheme 10). The reaction of cyanuric chloride with TPATTh yielded TTPATTh (99.59%), which is far more than that of TPATCz (TTPATCz, 47.03%).…”
Section: Friedel-crafts Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2e). [67][68][69][70] This methodology is straightforward, cheap, and more atomefficient in comparison to other pathways. The obtained CTFs also possess high thermo-chemical stability in a variety of aqueous and organic solvents.…”
Section: Other Synthesis Methodsmentioning
confidence: 99%
“…6,12,13 Conventional C C coupling syntheses of thiophene-based CMPs have been put into effect by transition-metal catalyzed reactions, for instance, Sonogashira-Hagihara reactions, [8][9][10][14][15][16][17][18][19][20] Suzuki-Miyaura reactions, 18,[21][22][23] and Stille reactions. 11,24 Other coupling reactions are also widely used in the preparation of thiophene-based CMPs, for example, Schiff-base reversible condensation, [25][26][27][28] Friedel-Crafts arylation, 29,30 hypercrosslinked, 31,32 nucleophilic substitution, 33 trimerization of cyano 34,35 reactions. However, most of these reactions involve multiple steps of the functionalization of building blocks.…”
Section: Introductionmentioning
confidence: 99%